A recyclable silica gel-supported schiff-base palladium nanocatalyst for suzuki-miyaura coupling and green organic synthesis - Shaheen M. Sarkar; Md Lutfor Rahman; Kamrul Hasan; Md. Maksudur Rahman Khan; Mohammed Salim Akhter; Emmet J. OReilly (Elsevier B.V., 2025)
We developed a cost-effective silica gel-supported Schiff-base palladium nanocatalyst (Si@SBPdNPs 3) using a novel three-step synthesis. First, silica gel was functionalized with an aminosilane compound, followed by Schiff base formation through reaction with 1,10-phenanthroline-2,9-dicarboxaldehyde. Palladium nanoparticles were then introduced using hydrazine hydrate as the reducing agent. FT-IR and XRD confirmed successful functionalization, while SEM images revealed spherical silica particles averaging 50 µm in diameter. TEM analysis showed well-dispersed palladium nanoparticles with an average size of 5.93 ± 0.1 nm. ICP and EDX data indicated a palladium loading of 0.023 mol%, and XPS analysis confirmed the presence of Pd(0) coordinated with the Schiff base ligand. The nanocatalyst demonstrated outstanding activity in Suzuki-Miyaura cross-coupling reactions under mild conditions, efficiently coupling various aryl halides with organoboronic acids to afford high product yields. It also proved effective in synthesizing the biologically active fungicide Boscalide. Moreover, the catalyst could be recovered and reused up to six times with minimal loss of activity, underscoring its sustainability and environmental compatibility. This robust, recyclable nanocatalyst offers a promising, scalable approach for C–C bond formation, with broad potential for applications in green and economical organic synthesis.